2022
DOI: 10.1021/acsami.1c24529
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene/Acid Binary Systems for Colorimetric Humidity Sensing with Reversibility, High Sensitivity, and Tunable Colors

Abstract: Humidity sensors are important for humidity detection in many storage and manufacturing processes. Issues like sensibility, response rate, controllability, and material and preparation process costs need to be taken into consideration for practical applications. Herein, we report an investigation on a series of azobenzene/acid binary systems using easily accessible compounds, whose thin films display reversible and widely tunable color changes in response to humidity stimulation, with high sensitivity, fast co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32] We selected azopolymers for photopatterning because they have interesting photoresponsive properties for the preparation of complex patterns. [33][34][35][36][37][38] In addition, we recently reported that some azopolymers exhibited photo induced reversible solid-to-liquid transitions. [39,40] Photonic structures were imprinted on the photoliquefied regions of these azopolymers.…”
Section: Doi: 101002/adma202202150mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32] We selected azopolymers for photopatterning because they have interesting photoresponsive properties for the preparation of complex patterns. [33][34][35][36][37][38] In addition, we recently reported that some azopolymers exhibited photo induced reversible solid-to-liquid transitions. [39,40] Photonic structures were imprinted on the photoliquefied regions of these azopolymers.…”
Section: Doi: 101002/adma202202150mentioning
confidence: 99%
“…Such colorimetric azobenzene sensors have been used to detect several metal cations, such as Hg 2+ [40], Al 3+ [41], Cu 2+ [42], Pb 2+ [43] as well as organic molecules relevant to applications in biology, such as sugar [44] and cysteine [45]. Li et al recently demonstrated sensors for humidity based on the deprotonation of protonated azobenzenes in azobenzene/acid binary systems [46]. Fast response of 2.3 s to full color change and tunable colors were reported, and monitoring of human breathing was raised as the most promising application.…”
Section: Azobenzenes For Chemical Sensingmentioning
confidence: 99%
“…The majority of chemical sensing with azobenzenes is solution-based where both the indicator azobenzene and the analyte are dissolved into water or mixtures of water and an organic solvent, such as acetonitrile or ethanol [40-43, 45, 47]. In some cases, the indicator has been bound to a solid material by embedding to silica [40] or covalently linking it to a suitable polymer, [57] creating convenient sensors for the detection of ionic species in solution or simply used as a paint to cover glass plates to create a humidity sensor [46]. Solid polymers enable additional specificity for the sensing as demonstrated in highly selective sensing of bisphenol A by molecular imprinted azobenzene polymers [55].…”
Section: Azobenzenes For Chemical Sensingmentioning
confidence: 99%
“…Switchable and adjustable transparency materials have crucial applications, such as sensors, bendable medical devices, anticounterfeiting devices, or smart windows. With the rapid development of modern materials science, researchers have successfully prepared various kinds of transparent and adjustable materials, the most studied of which are gel materials. At present, most of the investigations on gel materials have been carried out to achieve dynamic switching of transparency in different contexts through thermal, electrical, , and nature stimuli .…”
Section: Introductionmentioning
confidence: 99%